2002
DOI: 10.1002/ajmg.10319
|View full text |Cite
|
Sign up to set email alerts
|

Decisions about amniocentesis by advanced maternal age patients following maternal serum screening may not always correlate clinically with screening results: Need for improvement in informed consent process

Abstract: We evaluated the prenatal diagnosis utilization patterns of advanced maternal age (AMA) patients who underwent serum screening to assess how screening results correlated with their decisions regarding amniocentesis. A 6-year review (1994-1999) of laboratory records identified 2,456 AMA patients who underwent multiple-marker serum screening. The relationship between screening results and patients' decisions on whether or not to undergo amniocentesis was assessed. Among the 841 AMA patients with positive screens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Of the eleven papers included, all were based on quantitative studies. Four papers included data collected in the United States (US) (Marini et al, 2002;Baker et al, 2004;Kuppermann et al, 2006;Nakata et al, 2010), one from South Africa (Urban et al, 2011), two from Canada (Humphreys et al, 2003;Kaiser et al, 2004), one from China (Lo et al, 2010), one from Portugal (Nazaré et al, 2011), one from Italy (Vergani et al, 2002) and one from Israel (Muhsen et al, 2010). In seven papers, the participants were solely women (Baker et al, 2004;Kaiser et al, 2004;Kuppermann et al, 2006;Lo et al, 2010;Nakata et al, 2010;Urban et al, 2011;Vergani et al, 2002), whereas Nazaré et al (2011) andHumphreys et al (2003) included women and their partners (in the remaining two papers counselling was not mentioned).…”
Section: Study Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Of the eleven papers included, all were based on quantitative studies. Four papers included data collected in the United States (US) (Marini et al, 2002;Baker et al, 2004;Kuppermann et al, 2006;Nakata et al, 2010), one from South Africa (Urban et al, 2011), two from Canada (Humphreys et al, 2003;Kaiser et al, 2004), one from China (Lo et al, 2010), one from Portugal (Nazaré et al, 2011), one from Italy (Vergani et al, 2002) and one from Israel (Muhsen et al, 2010). In seven papers, the participants were solely women (Baker et al, 2004;Kaiser et al, 2004;Kuppermann et al, 2006;Lo et al, 2010;Nakata et al, 2010;Urban et al, 2011;Vergani et al, 2002), whereas Nazaré et al (2011) andHumphreys et al (2003) included women and their partners (in the remaining two papers counselling was not mentioned).…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Six papers reported prospective studies (Vergani et al, 2002;Humphreys et al, 2003;Kaiser et al, 2004;Kuppermann et al, 2006;Muhsen et al, 2010;Nazaré et al, 2011), four reported retrospective studies (Marini et al, 2002;Baker et al, 2004;Nakata et al, 2010;Urban et al, 2011) and Lo et al (2010) utilised both prospective and retrospective approaches. Four studies were survey-based (Humphreys et al, 2003;Kuppermann et al, 2006;Muhsen et al, 2010;Nazaré et al, 2011).…”
Section: Study Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…While research suggests that women can effectively incorporate such risk information into their decision making, [11] decisions regarding amniocentesis are influenced by the a priori risk level, [12] and do not appear to always correlate clinically with the test results received. [13,14] Of course, personal beliefs also influence decisions about invasive testing, including confidence that the results would not change behavior, mistaken beliefs that "negative" screening test results imply no risk, [15,16] and failures of the screening test to reassure. [15] In addition to these factors, however, the format used to present screening test results to women appears to directly impact decision making.…”
Section: Commentmentioning
confidence: 99%